2020
DOI: 10.1371/journal.pone.0228461
|View full text |Cite
|
Sign up to set email alerts
|

Interactive molecular dynamics in virtual reality for accurate flexible protein-ligand docking

Abstract: Simulating drug binding and unbinding is a challenge, as the rugged energy landscapes that separate bound and unbound states require extensive sampling that consumes significant computational resources. Here, we describe the use of interactive molecular dynamics in virtual reality (iMD-VR) as an accurate low-cost strategy for flexible protein-ligand docking. We outline an experimental protocol which enables expert iMD-VR users to guide ligands into and out of the binding pockets of trypsin, neuraminidase, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 66 publications
0
62
0
Order By: Relevance
“…In this work, we have demonstrated that iMD-VR is an effective tool for generating structures of complexes of the SARS-CoV-2 Mpro with an inhibitor-and an oligopeptide substrate. In previous work [31] we have shown that even novice users can quickly generate structures in good agreement with crystal structures, with minimal guidance. With a little practice, researchers can dock ligands to proteins in a few minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we have demonstrated that iMD-VR is an effective tool for generating structures of complexes of the SARS-CoV-2 Mpro with an inhibitor-and an oligopeptide substrate. In previous work [31] we have shown that even novice users can quickly generate structures in good agreement with crystal structures, with minimal guidance. With a little practice, researchers can dock ligands to proteins in a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…traditional screen/mousebased methods. [29] We believe that such technologies will find widespread application in structure-based drug design [31], in other molecular modelling, design and simulation applications, and in education. [33] IMD-VR should be directly useful in ongoing efforts to develop Mpro inhibitors as potential antivirals against COVID-19, especially as others look to crowd-source the problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, VR technology started to be significantly used for educational and research purposes in hard sciences such as mathematics, physics and chemistry [21–25] . In chemistry, especially, researchers have proposed VR tools to visualize quantum mechanics and molecular dynamics simulation results or to teach experiments in immersive and interactive way [26–32] …”
Section: Energy Storage and Virtual Realitymentioning
confidence: 99%
“…iMD-VR simulations were run similarly to the process described in previous work [5], including the use of trace atoms to act as a visual guide to the user. Trace atoms for the small ligand and substrate were extracted directly from PDB file 6W63 and 2Q6G, respectively.…”
Section: Trace Atom Placementmentioning
confidence: 99%